The Implementation of Student Team Achievement (STAD) Cooperative Learning Model in Traditional Vocal Subject of North Sumatra - Lamhot B. Sihombing (Britain International for Academic Research (BIAR) Publisher, 2020)
This study aims to determine the application of the STAD model of cooperative learning in learning the songs of the North Sumatra region in semester 2 students in the music education program at Universitas Negeri Medan. The problems to be discussed are: How is the application of the STAD model of cooperative learning in analyzing the main melodies of North Sumatra regional songs and how are the learning outcomes using the STAD model of cooperative learning methods. This study uses two approaches namely quantitative and qualitative methods with data collection techniques in the form of literature studies, observations, interviews, tests in the form of pre-test and post-test as well as analyzing learning outcomes. After the classroom action research process, the results were obtained that: in the application of the STAD model of cooperative learning in the material analysis of the main melodic form of North Sumatra regional songs in the second semester students of music education study program, it showed positive results and showed an increase in students' abilities. This is done for several stages, namely through cycle I and cycle II. In the trial test, the pre-test grade averages 52.3. The average grade that has been obtained is very low. Then conducted an experiment with a cycle I (post- test I) then the average grade increased by 66.33 but was declared incomplete. Furthermore, it is done by cycle II (post-test II), then the total number of class grades is increasing, amounting to 79.5 so that the value is declared complete and the cycle is not resumed. So, it can be concluded that the application of the STAD model of cooperative learning in learning the songs of the North Sumatra region in semester 2 students in music education study program has increased learning outcomes. This shows that STAD type cooperative learning can be used as an alternative in improving student learning outcomes in vocal learning of North Sumatra regional songs.